TANGGUNG JAWAB DANA PENSIUN BANK NAGARI DALAM PEMBAYARAN MANFAAT PENSIUN KEPADA PARA PESERTA - Tamba, Imelda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The pension fund is one of the potential event, which can be a source of national development supporting all Indonesian people. With the Pension Fund, the sustainability of income in old age can be realized, employees can work more quietly, and the expected productivity and employee loyalty can meningkat.Dana Bank Nagari Retirement Pension Fund is established by Bank Nagari with a view to organizing Defined Benefit Pension Fund and with the aim of providing continuity of income for participants after full devotion. Therefore, it can not be separated from the responsibility of the Pension Fund for the adequacy of funds to meet the obligations to pay retirement benefits to participants and parties entitled to pension benefits.